English church monuments in the Middle Ages history and representation - Saul, Nigel (Oxford University Press, 2009)
This is a comprehensive survey of English medieval church monuments. It examines all types of monument-cross slabs brasses, incised slabs, and sculpted effigies. It analyzes them in an historical context to show what they reveal of the self image and religious aspirations of those they commemorate.